1994
DOI: 10.1056/nejm199409083311004
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemic of Pneumococcal Disease in an Overcrowded, Inadequately Ventilated Jail

Abstract: Severe overcrowding, inadequate ventilation, and altered host susceptibility all contributed to this outbreak of pneumococcal disease in a large urban jail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
3
7

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(155 citation statements)
references
References 30 publications
6
137
3
7
Order By: Relevance
“…Crowding was particularly a risk factor for pneumonia in households that were not cross-ventilated, which is consistent with data from Hoge and colleagues, 20 who showed that the rates of S. pneumoniae incidence were highest in prison cell environments that were both crowded and poorly ventilated, compared with prison cells that did not share both of these risk factors. Crowding may be addressed in the long term by increasing the space allocated to households with large numbers of people, and reducing household size; by reducing the total fertility rate of women of child-bearing age, Bangladesh has made substantial strides in reducing household size.…”
supporting
confidence: 80%
“…Crowding was particularly a risk factor for pneumonia in households that were not cross-ventilated, which is consistent with data from Hoge and colleagues, 20 who showed that the rates of S. pneumoniae incidence were highest in prison cell environments that were both crowded and poorly ventilated, compared with prison cells that did not share both of these risk factors. Crowding may be addressed in the long term by increasing the space allocated to households with large numbers of people, and reducing household size; by reducing the total fertility rate of women of child-bearing age, Bangladesh has made substantial strides in reducing household size.…”
supporting
confidence: 80%
“…The multiple BTs found from this outbreak are consistent with ongoing transmission (i.e., growth and mutation) of the bacteria in a community over a period of time and contrasts with the indistinguishable BTs from the institutional outbreaks of 12F disease identified previously in Texas (1989) (22), Maryland (1992 with a single exception) (23), and California (2004) (19,24). Most pneumococcal outbreaks reported in the recent literature were short lived (1 to 2 months) and occurred among closed or institutional populations such as day care or military groups (7).…”
Section: Discussionmentioning
confidence: 78%
“…The resulting mosquito population boom is complemented by the high human population density in such situations, increasing the chances of stable transmission cycles between infected and susceptible persons. Even in industrialized countries, e.g., the United States, infections such as tuberculosis can spread through high-population density settings (e.g., day care centers or prisons) (12,(26)(27)(28).…”
Section: Changes In Human Demographics and Behaviormentioning
confidence: 99%